"I do not know the advantages of having a general practitioner" - a qualitative study exploring the views of low-acuity emergency patients without a regular general practitioner toward primary care - Lisa Kümpel; Sarah Oslislo; Rebecca Resendiz Cantu; Martin Möckel; Christoph Heintze; Felix Holzinger (BMC, 2024)
Abstract Background Emergency departments (ED) worldwide have to cope with rising patient numbers. Low-acuity consulters who could receive a more suitable treatment in primary care (PC) increase caseloads, and lack of PC attachment has been discussed as a determinant. This qualitative study explores factors that contribute to non-utilization of general practitioner (GP) care among patients with no current attachment to a GP. Method Qualitative semi-structured telephone interviews were conducted with 32 low-acuity ED consulters with no self-reported attachment to a GP. Participants were recruited from three EDs in the city center of Berlin, Germany. Data were analyzed by qualitative content analysis. Results Interviewed patients reported heterogeneous factors contributing to their PC utilization behavior and underlying views and experiences. Participants most prominently voiced a rare need for medical services, a distinct mobility behavior, and a lack of knowledge about the role of a GP and health care options. Views about and experiences with GP care that contribute to non-utilization were predominantly related to little confidence in GP care, preference for directly consulting medical specialists, and negative experiences with GP care in the past. Contrasting their reported utilization behavior, many interviewees still recognized the advantages of GP care continuity. Conclusion Understanding reasons of low-acuity ED patients for GP non-utilization can play an important role in the design and implementation of patient-centered care interventions for PC integration. Increasing GP utilization, continuity of care and health literacy might have positive effects on patient decision-making in acute situations and in turn decrease ED burden. Trial registration German Clinical Trials Register: DRKS00023480; date: 2020/11/27.